2009
DOI: 10.1071/ch09215
|View full text |Cite
|
Sign up to set email alerts
|

Control of Particle Morphology in Ab Initio RAFT Mediated Emulsion Polymerization

Abstract: Recent advances in the use of reversible addition–fragmentation chain transfer (RAFT) polymerization in dispersed phase systems have paved the way for the fine control of the morphology of latex particles that was not possible by conventional free radical polymerization techniques. With this approach, living amphiphilic block copolymers are synthesized that self-assemble to form micelles. The hydrophilic segment is formed from a water-soluble monomer which stabilizes the latex particles as polymerization proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Charged polymers, polyelectrolytes, have a fascinating ability to interact with their environment. Short polyelectrolyte chains, oligoelectrolytes, have been used to stabilize emulsions [1] and play a key role in paints and coatings, [2][3][4] controlled mineralization [5][6][7] as well as other applications. [8] This article proposes new and advanced characterization of these oligoelectrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Charged polymers, polyelectrolytes, have a fascinating ability to interact with their environment. Short polyelectrolyte chains, oligoelectrolytes, have been used to stabilize emulsions [1] and play a key role in paints and coatings, [2][3][4] controlled mineralization [5][6][7] as well as other applications. [8] This article proposes new and advanced characterization of these oligoelectrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Following this, a short n BuA or St block was included in the macro-RAFT agent to introduce amphiphilicity into the CTA and to prevent the initial formation of droplets. 133 The group prepared PAA-b-P n BuA-b-PSt-b-P n BuA and PAA-b-PSt-b-P( n BuA-co-MMA) from PAA-b-P n BuA-TTC and PAA-b-PSt-TTC macro-RAFT agents, respectively, although no macromolecular characterisation was provided to compare to their earlier study. Luo et al also adopted PAA-b-PSt-TTC as a macro-RAFT agent and surfactant in a sequential aqueous emulsion route to PSt-b-P n BuA-b-PSt (SBAS).…”
Section: An Industrially-attractive Continuous Miniemulsion Was Emplomentioning
confidence: 99%
“…102 Sprone et al later demonstrated means by which to influence the identity of core and shell blocks within symmetric PSt-b-P n BuA and PSt-b-(P n BuA-co-PMMA) particles. 133 Although the more hydrophobic PSt energetically prefers to form the particle core, using PAA-b-P n BuA-TTC produced core-shell particles with P n BuA cores. Alternatively, using PAA-b-PSt-TTC resulted in unusual deformed particles with mixed shells comprising inclusions of PSt amongst domains of the more hydrophilic P n BuAco-PMMA.…”
Section: Raftmentioning
confidence: 99%
See 1 more Smart Citation
“…Sprong et al [19] show that particle morphology developed in ab initio RAFT emulsion polymerization depends on the nature of the amphiphilic macro RAFT agent used. Destarac et al [20] examine thermoresponsive amphiphilic block copolymers prepared with xanthate RAFT agents (MADIX) as stimuli responsive emulsion stabilizers.…”
Section: Research Frontmentioning
confidence: 99%